Natural Infection with Rabies Virus: A Histopathological and Immunohistochemical Study of Human Brains - Firouzeh Farahtaj; Leila Alizadeh; Alireza Gholami; Alireza Tahamtan; Sadegh Shirian; Maryam Fazeli; Amir Sasan Mozaffari Nejad; Ali Gorji; Hamid Mahmoudzadeh Niknam; Amir Ghaemi (Osong Public Health and Research Perspectives, 2019)
Objectives Despite all the efforts and increased knowledge of rabies, the exact mechanisms of infection and mortality from the rabies virus are not well understood. To understand the mechanisms underlying the pathogenicity of rabies virus infection, it is crucial to study the tissue that the rabies virus naturally infects in humans. Methods Cerebellum brain tissue from 9 human post mortem cases from Iran, who had been infected with rabies virus, were examined histopathologically and immunohistochemically to evaluate the innate immune responses against the rabies virus. Results Histopathological examination revealed inflammation of the infected cerebellum and immunohistochemical analyses showed an increased immunoreactivity of heat shock protein 70, interleukin-6, interleukin-1, tumor necrosis factor-alpha, caspase-3, caspase-9, toll-like receptor3 and toll-like receptor4 in the infected brain tissue. Conclusion These results indicated the involvement of innate immunity in rabies infected human brain tissue, which may aggravate the progression of this deadly disease.